Pilot study investigating the effectiveness of cognitive rehabilitation therapy with patients with schizophrenia with a forensic history - Dodds, Julie (The University of Edinburgh, 2009)
Objectives: To evaluate the effectiveness of cognitive rehabilitation therapy with patients with schizophrenia within a forensic population. The intervention aimed to improve domains of cognitive functioning which have been found to be impaired as a result of schizophrenia. Forensic patients with schizophrenia have been found to have greater impairments in cognitive functioning relative to non-violent patients. Therefore interventions which target these deficits are important in rehabilitation interventions. Design: A within subject repeated design was used. A control measure was also implemented which involved patients being used as their own control. Method: 17 participants successfully completed the cognitive rehabilitation intervention. Initially 23 participants were recruited. Participants received approximately five hours of the computer-assisted cognitive remediation administered over seven weekly sessions. Outcome measures were cognitive assessments measuring executive functioning, attention, verbal learning and memory, perceptual organisation and visual memory. Outcome measures were administered pre-intervention, during treatment, post treatment and at three months follow up. A control assessment was also administered prior to the commencement of the intervention. Results: Post treatment measures on attention, perceptual organisation, visual memory and aspects of executive functioning were found to be significantly improved in comparison to pre intervention and control assessments. At 3 month follow up these improvements in cognitive functioning were found to be sustained. Conclusion: The pilot study indicated that cognitive rehabilitations are effective in improving cognitive functioning within forensic populations with schizophrenia. These results have the potential to improve functional outcomes and recovery, which could indirectly improve symptoms and risk of future violence. Further research is required in this area to provide additional evidence for this intervention to be available to forensic patients with schizophrenia.
Keywords: cognitive rehabilitation therapy; schizophrenia; cognitive remediation; forensic patients